Factors Affecting the Incidence of Ptosis after Trabeculectomy - Emine Malkoç Şen; Kübra Serbest Ceylanoğlu (Türk Oftalmoloji Dergisi, 2023)

(untitled)
Objectives:The aim of this study was to investigate the incidence of postoperative ptosis after primary trabeculectomy and the possible factors contributing to ptosis.Materials and Methods:A total of 312 patients (339 eyes) who underwent trabeculectomy with mitomycin-C between 2015 and 2020 were retrospectively evaluated. Patients who had regular follow-up for at least 6 months and no history of ptosis or ptosis surgery were included. Age, sex, glaucoma type, preoperative and postoperative intraocular pressure, preoperative and postoperative antiglaucoma medications, number of antiglaucoma drops, duration of antiglaucoma medication use, history of eye itching due to antiglaucoma medication-associated allergy, duration of follow-up, postoperative needling, needling time, and ocular massage were recorded. Ptosis was defined as ≥2 mm reduction in margin-reflex distance 1 from preoperative levels. Ptosis that had not improved for at least 6 months was considered persistent ptosis. Multivariate logistic regression was used to determine potential predictors of ptosis development.Results:Ptosis after trabeculectomy was observed in 35 of 339 eyes (10.3%). Thirty eyes of 30 patients (8.8%) had transient ptosis and 5 eyes of 4 patients (1.5%) had persistent ptosis. Preoperative duration of antiglaucoma medication use, drug(s) used (prostaglandin analogs, beta-blockers, alpha-2 agonists, carbonic anhydrase inhibitors, or combinations of these), needling time, and ocular massage after trabeculectomy did not differ significantly between groups (p>0.05). Rates of needling and eye itching due to antiglaucoma medication-associated allergy were significantly higher in patients with ptosis (p<0.05).Conclusion:Ptosis after trabeculectomy is an important problem for glaucoma patients. It has been observed that needling and a history of eye itching due to antiglaucoma drug-associated allergy may increase the risk of ptosis.